Education Exchange Storage Protocol: Transformation Into Decentralized Learning Platform - Rahardja, Untung; Ngadi, M. A; Budiarto, Rahmat; Aini, Qurotul; Hardini, Marviola; Oganda, Fitra Putri (Frontiers in Education, 2021)
The current micro-teaching process is readily online, and it is functional anywhere and anytime ubiquitously. All or most teaching and learning activities are accessible in centralized storage. However, centralized storage has inherent problems, such as a single point of failure with many possible data breaches, much duplication of data stored repeatedly in one location, and the lack of trust in third parties for data stored in centralized storage. Further issues include the high cost and low performance of the online systems that hinder the quality of the education process. In this paper, we propose a new framework Education Exchange Storage Protocol (EESP). EESP aims to improve the efficiency of the decentralized storage ecosystem in micro-teaching, coupled with blockchain technology acting as a control layer. Blockchain empowers the decentralized system by bringing together the most incompatible unstructured entities and integrate them. The decentralized storage system is armed with a blockchain smart contract that acts as a control layer, featuring impregnable security, immutability, trace-ability, and transparency. The EESP framework aims to elevate teaching and learning through blockchain decentralized storage systems in a transformational way, including but not limited to things like micro-credential, massive open online courses, and gamification, all in a single immersive learning platform. Finally, we tested and evaluated this framework using the truffle simulator, and the results demonstrate that the EESP model significantly improves performance.